Images of American society : a history of the United States - Lillibridge, George D. (Boston, Massachusetts : Houghton Mifflin Company, 1976)
The purpose of the Profile has been to use the life of one person to suggest the topic of the chapter and at the same time to remind the reader of the fact that American history is in the last analysis the story of individual human beings - the great and the obscure alike.
Part One. The foundations of American civilization -- Part Two. The new nation.
Includes index.
Keywords: HISTORY -- AMERICAN SOCIETY